The Effectiveness of Lavender Aroma Therapy for Better Quality of Sleep in Pregnant Women: Meta-Analysis - Teha, Zadia Dara Cynintya; Budihastuti, Uki Retno; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Sleep is a state of natural rest for the body that must be fulfilled every day. Sleep patterns of each individual are always different depending on age, lifestyle, environment, activities and health conditions. This study aims to analyze the primary study of the effectiveness of lavender aromatherapy to improve sleep quality in pregnant women with a meta-analysis. Subjects and Method: This study is a systematic review and meta-analysis with PICO as follows Population: pregnant women, Intervention: Giving lavender aromatherapy, Comparison: No aromatherapy given Outcome: Sleep quality. The articles used in this study were obtained from three databases, namely: Google Scholar, Pubmed, Science Direct with a time span between 2015-2022. The keywords used are “Lavender aromatherapy effect OR improving the quality of sleep AND pregnant AND Randomized Controlled Trials”. The articles were provided in full text in English and Indonesian, with a Randomized Controlled Trial study design and reporting on the Mean and SD in a multivariate analysis. The selection of articles was done by using a prism flow diagram. Articles were analyzed using the Review Manager 5.3 aplikasi application. Results: A total of 9 randomized controlled trials originating from Iran and Indonesia were selected for a systematic review and meta-analysis. The data collected showed the effectiveness of aromatherapy on improving sleep quality in pregnant women was 0.38 times that of pregnant women who were not given aromatherapy (SMD= 0.38; 95% CI= 0.38 to 0.55) and statistically significant p=0.004. Conclusion: Giving lavender aromatherapy can improve sleep quality in pregnant women. Keywords: aromatherapy lavender, sleep quality in pregnant women, meta-analysis. Correspondence:Zadia Dara Cynintya Teha. Master’s Program in Public Health, Universitas Sebelas Maret. Jl.Lawu raya Seturan Caturtunggal Depok Sleman Yogyakarta 55281, Indonesia. Email: Cynintya@gmail.com. Mobile: +6283857619108.